Las guantadas y el orden moral en la Nueva España. Primera parte del siglo XVIII - Lourdes Somohano Martínez (Nuevo mundo - Mundos Nuevos, 2006)
This text analyses three inquisitorial cases which deal with women accused of witchcraft in New Spain in the first half of the XVIIIth century. Many kinds of violence – physical, psychological and institutional – are identified. They reveal the profile of the women accused of this kind of crime as well as the mechanisms locally used to mold the Christian feminine ethic.